2020
DOI: 10.21037/atm.2020.01.31
|View full text |Cite
|
Sign up to set email alerts
|

Yin Zhi Huang, a traditional Chinese herbal formula, ameliorates diet-induced obesity and hepatic steatosis by activating the AMPK/SREBP-1 and the AMPK/ACC/CPT1A pathways

Abstract: Background: Yin Zhi Huang (YZH) is a formula composed of Artemisia scoparia, Gardeniae fructus, Scutellaria baicalensis Georgi, and Lonicerae Japonicae Flos. Most of the components are eaten as food in Asia. Here, we evaluated the role of YZH on a high-fat diet (HFD)-induced obesity and hepatic steatosis.Methods: Male C57BL/6J mice were fed with normal-chow diet, HFD, and HFD with low-or high-dose YZH for 16 weeks. Body weight gain, adipose mass, and plasma lipids levels were measured to evaluate the effect of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(15 citation statements)
references
References 41 publications
1
14
0
Order By: Relevance
“…Apart from regulating the gene transcription of white adipose tissue (WAT) to adapt to the systemic energy regulation, it can also affect the differentiation and remodeling of brown adipose tissue (BAT) by regulating the activity of PGC-1α and PPAR-γ factors ( 29 31 ). AMPK acts as an energy regulator, and requires activation to exert anti-obesity effects in the surrounding tissues ( 32 , 33 ). ACC is the downstream factor of AMPK, and it often plays an essential role on fatty acid metabolism ( 34 ).…”
Section: Discussionmentioning
confidence: 99%
“…Apart from regulating the gene transcription of white adipose tissue (WAT) to adapt to the systemic energy regulation, it can also affect the differentiation and remodeling of brown adipose tissue (BAT) by regulating the activity of PGC-1α and PPAR-γ factors ( 29 31 ). AMPK acts as an energy regulator, and requires activation to exert anti-obesity effects in the surrounding tissues ( 32 , 33 ). ACC is the downstream factor of AMPK, and it often plays an essential role on fatty acid metabolism ( 34 ).…”
Section: Discussionmentioning
confidence: 99%
“…In an insulin resistance C57BL/6J mice model, Yin Zhi Huang has associated with a decrease of AMPK/SREBP-1 pathway-mediated de novo lipogenesis and an increase of AMPK/ACC/CPTI pathwaymediated mitochondrial fatty acid β oxidation to ameliorate insulin resistance and facilitate lipid metabolism [64]. In current study, we found that miR-148a-3p inhibited AMPK to phosphorylate ACC activating its' ability to convert malonyl-CoA from acetyl-CoA consequently decreased CPT1C content to reduce mitochondrial fatty acid oxidation.…”
Section: Discussionmentioning
confidence: 99%
“…ACC accelerates FAO in two CPT1dependent manners. On the one hand, phosphorylation of ACC inactivates the ability to mediate malonyl-coA production, which promotes FAO with increased CPT1A content [58]. On the other hand, the formation of a complex between ACCα and CPT1A attenuates in the case of glucose deficiency, which boosts FAO by facilitating the transport of FA [59].…”
Section: Acc-driven Lipogenesis Supports Cell Survival and Metastasis...mentioning
confidence: 99%